HUBUNGAN ANTARA BURNOUT DENGAN KESEJAHTERAAN PSIKOLOGIS PADA KARYAWAN GEN Z DI PERUSAHAAN STARUP AREA JAKARTA - Urip Rahmad Endarto; Untung Subroto Dharmawan (STKIP Subang, 2026)
Generation Z has become an increasingly dominant workforce in the modern workplace, particularly in startup companies characterized by dynamic, competitive, and demanding work environments. High job demands, pressure to achieve organizational goals, and fast-paced work routines may increase the risk of burnout among Generation Z employees, which can ultimately affect their psychological well-being. This study aims to examine the relationship between burnout and psychological well-being among Generation Z employees working in startup companies in Jakarta. A quantitative research design was employed using the Oldenburg Burnout Inventory (OLBI) to measure burnout and Ryff’s Psychological Well-Being Scale (RPWB) to assess psychological well-being. The sample consisted of 204 Generation Z employees working in startup companies in Jakarta, selected through convenience sampling. The results revealed a significant negative correlation between burnout and psychological well-being (r = −0.484, p < 0.05), indicating that higher levels of burnout are associated with lower levels of psychological well-being among employees.